K06 Uptake of Predictive Tests for Huntington's Disease (HD) in the UK 1993–2012. (17th September 2014) - Quarrell, O; Rosser, E; Taverner, N; Miedzybrodzka, Z; Clarke, A; Craufurd, D; Strong, M
Abstract : Background: Predictive testing based on CAG repeat length measurement has been available since 1993. Data on numbers of tests conducted at 23 genetic centres were available through a UK Huntington's Prediction Consortium. Aims: To determine the cumulative uptake of predictive tests for those at 50% risk in the UK. Methods: The numerator was the cumulative number of tests undertaken between 1993 and 2012. The denominator was the cumulative population at 50% risk. This was estimated from HD prevalence and ratio of number at risk to number affected using the method of Tassicker et al 2009. Prevalence estimates vary, so we analysed the data using 3 different values: 8, 10 and 12 × 10 –5 . We used two values for the ratio of affected cases to those at risk: 1:5 and 1:4.2. We used Tassicker et al 's estimate of 18.8 years for illness duration. Although minimal, missing data for 1994 to 2012 were imputed using standard techniques; data were not imputed for 1993 because of uncertainties about when centres started to offer predictive testing. Results: We produced a range of cumulative uptake percentages based on the different scenarios. If the prevalence is 10 × 10 –5 then the cumulative uptake of predictive tests after 20 years is approximately 18% based on a ratio of affected cases to those at risk of 1:5, and 21% based on a ratio of 1: 4.2. A prevalence of 12 × 10 –5 and ratio of 5 gave a cumulative uptake of approximately 15% whereas a prevalence of 8 × 10 –5 and ratio of 4.2 gave a cumulative uptake of approximately 26%. Conclusion: This complete analysis of all predictive tests conducted in the UK over a 20-year period confirms that uptake of predictive testing among those at high risk of HD is no more than approximately 15–26%.